Battles of the Thirty Years War - Guthrie, William P. (Greenwood Press, 2002)
Machine generated contents note: Preface ix – 1. Breitenfeld and the Thirty Years War 1 – 2. The Battle of White Mountain: First Battle of the Thirty Years War 47 – 3. The 1622 Campaign: The Battle of Wimpfen 83 – 4. The Battle of Stadtlohn: The End of the German War 105 – 5. The Danish War: Dessau and Lutter 117 – 6. Gustavus's Run of Victory: From Stettin to the Lech 149 – 7. Gustavus versus Wallenstein, 1632: Alte Veste and Lutzen 187 – 8. The War in Westphalia, 1632-33 233 – 9. The Battle of Nordlingen: From Lutzen to the Peace of Prague 259
12001-23844
Keywords: Wörterbuch; Thirty Years' War; 1618-1648; Battles; Military art and science